إعراب أسماء الله وصفاته وما يتعلق بذاته عز وجل: ضوابط وآداب (Issues related to Polite Dealing with the Names of Allah and His Attributes) - (Abdel Aziz Bin Hamid al-Juhaniy), عبد العزيز بن حميد الج (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: تتناول الدراسة أسماء الله الحسنى وصفاته، وقد رأى الباحث أن أسماء الله وصفاته جزء من اللغةـ، وينبغي أن يكون لها وضع خاص عند الاستعمال لدى الناس، بحيث يكون لها تعظيم وتقدير، ولا سيما عند تعامل اللغويين والدارسين معها في كتاباتهم وبحوثهم؛ ولذلك قامت هذه الدراسة بتتبع أوجه الإعراب المتعلقة بأسماء الله تعالى وصفاته، وما له علاقة بذاته سبحانه. وسوف تتناول الدراسة مسائل تتعلق بأدب التعامل مع أسماء الله مبتدئا بالأسماء ثم الأفعال ثم الحروف. ومن هذه القضايا: الضمير (نا)، وصفة جمع المذكر السالم، وبدل كل من كل، وفعل الأمر، وكان (فعل ماض)، والفعل المبني للمجهول، ولام العاقبة، ولا الناهية، ولام الأمر. الكلمات المفتاحية: الضمير(نا)-صفة جمع المذكر السالم-بدل كل من كل-فعل الأمر-لام الأمر. Abstract: This study deals with the names of Allah and His attributes. The researcher believes that the names of Allah and His attributes are part of the language, and should have a special status when used by people so that they have to increase their appreciation, especially linguists and scholars who deal with this issue in their writings and researches. Therefore, the present study keeps track of this different inflection on the names and attributes of Allah, and their relationship with the Almighty alone. The study will address issues related to polite dealing with the Names of Allah beginning with Names, verbs and particles. Among these issues: pronoun (Na), plural masculine description, and instead of all of all, imperative, verb (to be), and the passive verb, and lam for result, negative particle, and lam for command. Keywords: Pronoun (Na)- Plural Masculine Description- Instead of All of All- Imperative- Lam for Command. Abstrak: Kajian ini adalah mengenai nama-nama Allah dan sifat-sifatNya. Penyelidik melihat bahawa nama-nama Allah dan sifat-sifatNya merupakan sebahagian daripada bahasa. Justeru, ia seharusnya mendapat perhatian yang istimewa dari segi penggunaannya di kalangan orang ramai supaya mereka membesarkan nama-nama ini dan mengiktirafnya terutama ahli bahasa atau penuntut ilmu apabila menulisnya di dalam penyelidikan dan penulisan. Oleh yang demikian, kajian ini mengemukakan beberapa bentuk I’rab yang berkaitan dengan nama-nama Allah dan sifat-sifatNya serta kaitannya dengan zat-zat Allah. Di samping itu juga, kajian ini akan membahaskan tentang isu yang berkaitan dengan etika ketika menulis nama-nama Allah seperti penggunaan kata ganti nama (kami), sifat jamak muzakkar salim, badal kul min al-kul, kata perintah, kata kerja lampau (kana), kata kerja mabni al-majhul, Lam al-aqibah, la nahi, lam amar. Kata kunci: Kata Ganti Nama (Kami) – Sifat Jamak Muzakkar Salim – Badal Kul Min Al-Kul – Kata Perintah – Lam Amar.